2007
DOI: 10.3171/jns-07/11/0905
|View full text |Cite
|
Sign up to set email alerts
|

Management of bone-invasive, hyperostotic sphenoid wing meningiomas

Abstract: Sphenoid wing meningiomas frequently invade bone, although such invasion does not represent malignancy. These lesions are generally histologically benign. Total removal with a prospect for cure and visual preservation should be the goal of treatment. This requires extensive drilling of the invaded bone and extensive excision of the involved dura. When the optic canal is involved, it should be decompressed. Extensive bone resection should be followed by cranioorbital reconstruction for good cosmesis and to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 36 publications
3
109
0
Order By: Relevance
“…In addition to the dural-based mass, meningiomas promote hyperostosis of adjacent bone in up to 49% of all tumors [26,27]. Histopathology of hyperostotic bone demonstrates infiltration of meningothelial tumors cells within Haversian canals, suggesting that bony disease must be addressed to completely resect the tumor [28][29][30]. The rate of tumor infiltration in bone may be as high as 69% in skull base tumors [30].…”
Section: Origins Of Meningiomasmentioning
confidence: 99%
“…In addition to the dural-based mass, meningiomas promote hyperostosis of adjacent bone in up to 49% of all tumors [26,27]. Histopathology of hyperostotic bone demonstrates infiltration of meningothelial tumors cells within Haversian canals, suggesting that bony disease must be addressed to completely resect the tumor [28][29][30]. The rate of tumor infiltration in bone may be as high as 69% in skull base tumors [30].…”
Section: Origins Of Meningiomasmentioning
confidence: 99%
“…One small series of five patients with non-Hodgkin lymphoma of the skull base confirmed the difficulty in differentiating these neoplasms but suggested that bone enhancement without hyperostotic reaction and cavernous sinus invasion without narrowing of the carotid artery lumen could be helpful in distinguishing lymphoma from meningioma [9]. The latter is typically characterized by hyperostotic bone involvement which actually represents invasion of the bone by the tumor [10] and does not generally preserve the carotid artery lumen. These features appear to apply to our patient as radiography did not show a hyperostotic reaction to bone involvement and demonstrated delicate sparing of the carotid artery lumen in both MRI studies taken 8 weeks apart, despite growth of the tumor over this period.…”
Section: Discussionmentioning
confidence: 99%
“…These regions are often due to actual invasion of the bone with tumor, and aggressive surgical removal, when possible, is recommended[3]. Management of such lesions where the osteoblastic skull base may not be resectable from a purely endoscopic endonasal resection should include consideration for a bifrontal craniotomy to achieve higher rates of bony removal; although a gross total resection of the bony component could not be achieved in this case, maximum bony resection was performed without neurovascular injury through this approach.…”
Section: Discussionmentioning
confidence: 99%